The Influence of Financial Literacy and Financial Attitude on Financial Management of Generation Z in Suli District - Azila, Nur; Hapid, Hapid; Bachri, Samsul (PT. EQUATOR SINAR AKADEMIA, 2025)
Scale used is the Likert scale. The data analysis used is SPSS 30 static analysis and all variable hypotheses Generation Z is a generation group that was born and grew up in the digital era and has unique characteristics compared to previous generations. They are known as